Lifelong Learning in the Age of Data: Opportunities and Policy Impact - Dichaba, Mpho M. (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
This article entitled "Lifelong Learning in the Age of Data: Opportunities and Policy Impact", Author, Mpho M. Dichaba, published in Volume 9, Issue 1, pp 64-70 retracted by the publisher due to containing THE data without authorisation for use.